The Types of Non-Observance Maxims Performed by the Main Character in Knives Out Movie - Windu Gunatika; Komang Dian Puspita Candra; Ni Made Verayanti Utami (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
The situation in which people involved in a conversation failed to obey the maxims is known as the non-observance maxims. This research focuses on finding the types of non-observance maxims performed by the main character during the conversation in the Knives Out movie. The theory from Grice (1975), supported by Thomas (1995), applied to find out the types of non-observance maxims. The data of this research were collected by using the document analysis method and analysed by combining quantitative and qualitative methods. The finding presents that there are three types of non-observance maxims performed by the main character in the Knives Out movie. It consists of flouting maxim of relevance (50%), violating maxim of quality (37,5%), and violating maxim of relevance (12,5%). The finding explains that the main character in the Knives Out movie tend to break the maxim by giving an irrelevant answer compared to the topic of discussion. Keywords: maxims, non-observance maxims, knives out, types